ANALYSIS OF AREAL TYPES OF SPECIES OF THE GENUS SCUTELLARIA, DISTRIBUTED IN THE FLORA OF THE FERGHANA VALLEY - Akbarova Mukhayyo Khusanovna (Web of Journals Publishing, 2024)
This article presents an analysis of the results of scientific research conducted to determine the geography and types of habitat of species of the genus Scutellaria of the Lamiaceae family, widespread in the Fergana Valley. To analyze species by area types, classical and latest publications on the local flora of Central Asia were used. Based on the results of the research, the natural boundaries of the distribution of species of the genus Scutellaria common in the flora of the valley were established, and they were divided into 11 areal types. These habitat types, in turn, were divided into four habitat classes: Western Tien Shan (7), Pamir-Alai (5), Mountain Central Asian (10), Palaearctic (1). Of the 23 species of the genus Scutellaria common in the Fergana Valley, 22 species (96%) are Central Asian endemics, that is, they are recognized as centers of local speciation.
Keywords: Lamiaceae, Scutellaria, habitat type, habitat class, biogeographic spectrum, Mountainous Central Asian, endemic, subendemic.